INDUSTRIAL POLICY AND “NEW NORMALITY” - N. M. Abdikeev; A. Yu. Teplyakov (Управленческие науки, 2017)
This article examines the issues relating to the implementation of the industrial policy and the national economy reindustrialization under the conditions of so-called “new normality”. It is mentioned that the reasons for “new normality” is a global inability to design new forms of activity, which led to a deficit of non-toxic assets in excess of money supply. The slowdown and the decline of global economic growth are the signs of this process. As the main instrument for overcoming the economic stagnation “normality” the intensification of efforts to import substitution is offered. It is substantiated that based on export-raw commodity model the new Russia industrialization is not feasible, as the solution of the problem of high-tech import substitution. There is a need to design and organize in Russia new national industries that have advanced competitiveness in the world economy, as a mechanism for the withdrawal of the global economy beyond the “new normality”. It is proposed to counterpose the “new normality” of the national innovation policy and pay attention to issues related to the long-term innovation and industrial development of the Russian economy, both in the sectoral and regional contexts.